Digital Marketing Prototype of Electronic Growth Chart (e-KMS) - Sutantio, R. Alamsyah; Nurmawati, Ida; Muna, Niyalatul; Mudiono, Demiawan Rachmatta Putro; Wicaksono, Andri Permana; Muflihatin, Indah (International Journal of Health and Information System, 2024)
Currently, Indonesia is facing serious Multiple Nutritional Problems (MGG) with 30.8% stunting and 35.4% obesity rates. The Healthy Growth Card (KMS) serves as an instrument for growth monitoring, particularly related to nutritional status. Growth disturbances, such as malnutrition due to both nutritional deficiencies and excesses, can be detected early by plotting weight on the KMS. Websites are a form of internet marketing and an effective part of digital marketing for disseminating information and promoting products. This research aims to create a prototype for digital marketing electronic Growth Chart (e-KMS). The research employs the software system development method using the Prototype model. The prototype is designed using UML (Unified Modeling Language) and case tools. The digital marketing prototype is a website-based platform with capabilities for promoting and registering online at the Polytechnic Institute of Jember (Polije) Daycare, as well as serving as a Communication Information and Education (CIE) medium for assessing and monitoring the nutritional status of children in the form of e-KMS. Program coding is needed to make the prototype usable as a digital marketing tool for e-KMS, enabling the monitoring of children's growth to be implemented in childcare institutions.